STUDIES ON FUNCTIONAL BACTERIA OF INDONESIAN TROPICAL FOREST PLANTS FOR BIOREHABILITATION OF DEGRADED LANDS - Irnayuli R. Sitepu; Yasuyuki Hashidoko; Aryanto Aryanto; Maman Turjaman; Satoshi Tahara; Siti S. Miftahuliyah; Erdy Santoso (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2008)
Forest degradations have left vast amount of damaged and abandoned lands in Indonesia. In this paper, we present our approaches in rehabilitation of adverse soils using functional bacteria isolated from plant species of Indonesian tropical rain forests. For these purposes, we collected bacteria from various bio-geo-climatically different forests and conducted bioassays to test these bacterial abilities in improving plant growth. Repeated seedling-based studies on Shorea spp., Alstonia scholaris, Acacia crassicarpa, and Agathis lorantifolia have revealed that many bacteria were able to promote plant growth at early stage in the nursery. Various plant responses towards inoculations suggested that although forest soils maintain highly diverse and potent bacteria, it is necessary to select appropriate approaches to obtain optimum benefits from these plant-bacteria interactions. Our ideas and futures studies for further management of these plant- bacteria interactions for biorehabilitation are also discussed.